Directional Energy Migration in Nanoparticles of Crystalline Metal Complexes. (4th February 2015) - Previtera, Elia; Tissot, Antoine; Johns, Robert W.; Hauser, Andreas
Abstract : Size‐controlled micro‐ and nanocrystals of a [Ru(bpy)3 ][NaCr(ox)3 ] coordination network are prepared using reverse micelles. Compared with the bulk reference, the 2 E emission of the Cr(III) ions indicates an efficient directional energy migration toward the surface of the nanocrystals.